Dietary Different Replacement Levels of Fishmeal by Fish Silage Could Influence Growth of Litopenaeus vannamei by Regulating mTOR at Transcriptional Level - Shao, Jianchun; Wang, Lei; Shao, Xuqing; Liu, Mei (Frontiers in Physiology, 2020)
Fish silage has been confirmed as a high-quality feed ingredient because of its balanced nutrition, low cost and environmental friendliness. In the present study, we evaluated the performance of replacing fishmeal by fish silage (FS) in the diet of white shrimp, Litopenaeus vannamei. Five isonitrogenous (410 g kg-1) and isolipidic (75 g kg-1) diets were formulated with replacement of fishmeal by 0 (FM), 25 (FS25%), 50 (FS50%), 75 (FS75%) and 100% (FS100%) FS. After an 8-week trial, shrimps fed low FS diets (FM and FS25%) had significantly higher FW, WG and SGR (P < 0.05). No significant differences were found in body composition and most antioxidant enzyme activities of all groups (P > 0.05). Compared to high FS groups (FS75% and FS100%), low FS replacement levels (0 and 25%) had enhanced trypsin activity. And trypsin transcriptional level presented a similar trend with trypsin activity. In terms of intestinal histopathology, no obvious histological damage was observed in the intestine of all groups. tor and s6k of low replacement level groups (FM and FS25%) were significantly up-regulated (P < 0.05), which indicated activation of mTOR signaling pathway in low FS groups at transcriptional level. The enhanced performances of growth and mTOR signaling pathway in low FS groups (FM and FS25%) provided us some insights into the regulation mechanism of nutrient signal on growth. Based on above, dietary fish silage could influence growth of shrimp by regulating mTOR at transcriptional level and fish silage is a potential substitute of fishmeal in shrimp feed.